HUBUNGAN ANTARA KESELAMATAN KERJA DENGAN SEMANGAT KERJA KARYAWAN BAGIAN PRODUKSI CAHAYA TIMUR OFFSET YOGYAKARTA - Yulianto Triadityo, Doni (Universitas Ahmad Dahlan, 2012)
AbstractThis research is aimed to know the correlation between works safety and works spirit. Research subject is production employee at CV. Cahaya Timur Offset Yogyakarta. Method research in this study is use quantitative approach by using simple random sampling. Data collection tools in this study used works safety scale and works spirit scale. Methods of data analysis in this study used product moment correlation analysis techniques. The result of this research showed a significant correlation with rxy = 0,585 and p = 0,000 (p < 0.01). Effective amount donation given by works safety variable to works spirit variables was 34,2%. The result showed that there is significant positive correlation between works safety and works spirit of production employee at CV. Cahaya Timur Offset Yogyakarta. Hypothesis is accepted and showed that the higher works safety the higher works spirits and the opposite that the lower safety works, the lower also works spirits. Implementation of safety is on the medium level and the majority of subjects had a high work spirit in the high category.Key words : works safety, works spirit.